2013
DOI: 10.1074/jbc.m113.469783
|View full text |Cite
|
Sign up to set email alerts
|

The Epigenetic Modifier Ubiquitin-specific Protease 22 (USP22) Regulates Embryonic Stem Cell Differentiation via Transcriptional Repression of Sex-determining Region Y-box 2 (SOX2)

Abstract: Background: Ubiquitin-specific protease 22 (USP22) is a deubiquitylating enzyme with established biological functions in cancer cells. Results: USP22 drives differentiation of embryonic stem cells (ESCs) and represses sex-determining region Y-box 2 (SOX2) transcription. Conclusion: USP22 is induced during ESC differentiation to repress SOX2 transcription. Significance: Understanding the epigenetic programs that control changes in gene expression during the transition from self-renewal to differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 75 publications
(75 reference statements)
1
69
1
Order By: Relevance
“…Such a reduction could be driven by a variety of mechanisms, including RNF20 promoter hypermethylation 14 or increased expression of pertinent DUBs. 9,13,23,24 We previously reported that RNF20 silencing promotes the migration of non-transformed human mammary epithelial MCF10A cells, and facilitates transformation of mouse cells, consistent with a tumor-suppressive role. 14 Moreover, reduced levels of RNF20 and H2Bub1, observed in colitis and colorectal cancer in mice and humans, can increase the expression of cytokines via the NF-κB pathway, promoting chronic inflammation and colitis-associated colorectal cancer.…”
mentioning
confidence: 63%
“…Such a reduction could be driven by a variety of mechanisms, including RNF20 promoter hypermethylation 14 or increased expression of pertinent DUBs. 9,13,23,24 We previously reported that RNF20 silencing promotes the migration of non-transformed human mammary epithelial MCF10A cells, and facilitates transformation of mouse cells, consistent with a tumor-suppressive role. 14 Moreover, reduced levels of RNF20 and H2Bub1, observed in colitis and colorectal cancer in mice and humans, can increase the expression of cytokines via the NF-κB pathway, promoting chronic inflammation and colitis-associated colorectal cancer.…”
mentioning
confidence: 63%
“…2,3,25,[48][49][50] However, knowledge regarding the precise mechanisms underlying how Sox2 is posttranslationally regulated remains limited. Several studies have shown that the protein activity of Sox2 can be modified by sumoylation, methylation, acetylation and phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, USP22 deubiquitinates intracellular protein, including the shelterin protein telomeric repeat binding factor 1 (4), the histone deacetylase sirtuin 1 (5) and the far upstream element-binding protein 1 fructose-1,6-bisphosphatase 1 (4), and therefore performs an extensive physiological function. A murine study showed that USP22 also regulates embryonic stem cell differentiation (6). In humans, the USP22 gene is located on chromosome 17, consists of 14 exons, and is transcribed and produced broadly across various tissues (7).…”
Section: Introductionmentioning
confidence: 99%